Bovine milk-derived exosomes for drug delivery. Issue 1 (1st February 2016) - Munagala, Radha; Aqil, Farrukh; Jeyabalan, Jeyaprakash; Gupta, Ramesh C.
Highlights: Bovine milk is a biocompatible and scalable source of exosomes. Milk exosomes can serve as a vehicle to deliver both hydrophilic and lipophilic small drug molecules. Exosomal formulations provide enhanced biological efficacy. Milk exosomes can be functionalized with ligands such as folic acid to achieve tumor targeting. Milk exosomes per se exhibit protective effects presumably due to the endogenous cargo of macromolecules. Abstract: Exosomes are biological nanovesicles that are involved in cell–cell communication via the functionally-active cargo (such as miRNA, mRNA, DNA and proteins). Because of their nanosize, exosomes are explored as nanodevices for the development of new therapeutic applications. However, bulk, safe and cost-effective production of exosomes is not available. Here, we show that bovine milk can serve as a scalable source of exosomes that can act as a carrier for chemotherapeutic/chemopreventive agents. Drug-loaded exosomes showed significantly higher efficacy compared to free drug in cell culture studies and against lung tumor xenografts in vivo . Moreover, tumor targeting ligands such as folate increased cancer-cell targeting of the exosomes resulting in enhanced tumor reduction. Milk exosomes exhibited cross-species tolerance with no adverse immune and inflammatory response. Thus, we show the versatility of milk exosomes with respect to the cargo it can carry and ability to achieve tumor targetability. This is the first report to identify a biocompatible and cost-effective means of exosomes to enhance oral bioavailability, improve efficacy and safety of drugs.